Tesis para ser publicada en la revista - Bustamante Ordóñez, Misshelle Alejandra (2014)
Deforestation is a problem of global concern that affects mainly tropical countries, contributing to the decrease of vegetation cover and diversity of ecosystems. An alternative to solving this problem is the recovery of forests through the establishment of seed sources and the genetic diversity evaluation of them. A species of great commercial interest is Juglans neotropica, which is in danger of extinction. In this study we assessed the diversity and genetic structure of two populations of Juglans neotropica in southern Ecuador through the application of AFLP markers. Three reagents optimization trials were tested. High levels of polymorphism and genetic differentiation were found in both populations